Prof. Dr. Iris Clemens and Prof. Dr. Dhruv Raina - Clemens, Iris; Raina, Dhruv (Cluster Conversations, 2023)
In this episode, Iris Clemens - Chair of Educational Science at the University of Bayreuth and Principal Investigator of the Africa Multiple Cluster of Excellence - talks with Prof. Dr. Dhruv Raina from the Jawaharlal Nehru University, New Delhi, where he teaches the history and philosophy of science. Together they are having a conversation about Prof. Raina's current research that he worked on during his fellowship at the Cluster - the evolution of the university system and the tranfer of knowledge on the African continent.